2008
DOI: 10.1016/j.freeradbiomed.2008.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen species in the neurotoxicity of environmental agents implicated in Parkinson's disease

Abstract: Among age-related neurodegenerative diseases, Parkinson's disease (PD) represents the best example for which oxidative stress has been strongly implicated. The etiology of PD remains unknown, yet recent epidemiological studies have linked exposure to environmental agents, including pesticides, with an increased risk of developing the disease. As a result, the environmental hypothesis of PD has developed, which speculates that chemical agents in the environment are capable of producing selective dopaminergic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
171
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(174 citation statements)
references
References 176 publications
(196 reference statements)
0
171
1
2
Order By: Relevance
“…Rotenone disrupts the mitochondrial electron-transport chain at complex I and causes acute ATP depletion and generation of massive ROS (Drechsel and Patel, 2008). This study has demonstrated the protective effect of hyperforin on attenuating rotenoneinduced cytotoxicity in differentiating CG-4 cells.…”
Section: Hyperforin Protects Cg-4 Cells From Rotenone-induced Atp Depmentioning
confidence: 56%
“…Rotenone disrupts the mitochondrial electron-transport chain at complex I and causes acute ATP depletion and generation of massive ROS (Drechsel and Patel, 2008). This study has demonstrated the protective effect of hyperforin on attenuating rotenoneinduced cytotoxicity in differentiating CG-4 cells.…”
Section: Hyperforin Protects Cg-4 Cells From Rotenone-induced Atp Depmentioning
confidence: 56%
“…A cell is able to overcome small perturbations and regain its original state; however, more severe oxidative stress can cause cell death, and even moderate oxidation can trigger apoptosis, while more intense stresses may causes necrosis (8) . SOD is one of the main antioxidant systems and is made up of three components: CuZn-SOD (SOD1) exists in the cytosol, Mn-SOD (SOD2) in the mitochondrial matrix, and extracellular SOD (SOD3) in the tissue as the secretory form (9) . Because the superoxide anion radical substrate poorly penetrates membranes, the SOD isoenzymes primarily exert their protective functions in their respective compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Factors There is evidence to suggest that environmental toxicants may cause some parkinsonism syndromes [72,73]. This hypothesis seems consistent with the fact that PD is now the second most common degenerative neuropsychiatric disorder (after the dementias), in contrast to its evident rarity in previous centuries [74].…”
Section: Environmentalmentioning
confidence: 72%